S100A8/A9 Proteins in Diseases of the Exocrine Pancreas - Ossig, Rainer; Schnekenburger, Jurgen (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2009)
The function of the exocrine pancreas is the production and secretion of digestive enzymes. Major pathologies of the exocrine pancreas are pancreatitis, a sterile inflammation, and pancreatic adenocarcinoma, a highly lethal tumor. Both diseases involve cells of the immune system and calcium binding proteins of the S100 family. Here, we review the known function of these proteins in pancreatitis and pancreas cancer. Few S100 proteins were detected during pancreatitis and only for the S100A8/A9 complex data are available that elucidate a presumable function. In a rodent model of caerulein-induced acute pancreatitis, pancreatic S100A8/A9 expression was exclusively detected in infiltrating leukocytes. S100A9 knockout animals developed less pancreatic tissue damage, no significant edema formation, and the intrapancreatic infiltration of leukocytes was inhibited. Purified S100A8/A9 dissociated calcium-dependent cell-cell contacts between pancreatic acinar cells in vitro and in vivo. These results indicate that the dissociation of epithelial cell-cell contacts mediated by secreted S100A8/A9 is crucial for the infiltration of leukocytes into the pancreas. Several studies revealed an expression of S100 proteins in pancreatic cancers. Especially S100A8/A9 proteins were found in myeloid cells within tumor-associated stroma. Whether these proteins contribute to a recruitment of specific immune cells to tumors or to other steps of pancreatic tumor progression is not clear. None of the S100 proteins has been clearly confirmed as a pancrea tumor marker. Taken together, S100A8/A9 proteins are essential for the inflammation induced infiltration of leukocytes in murine pancreatic tissue a mechanism which may also support tumor progression and metastasis.
Keywords: inflammation